Influence of Rice Husk Biochar on Soil Nematode Community under Upland and Flooded Conditions: A Microcosm Experiment - Nguyen Van Sinh; Risako Kato; Doan Thi Truc Linh; Nguyen Thi Kim Phuong; Koki Toyota (Agronomy, 2022)
Biochar has the potential for improving soil properties and supporting ecological functions, but it has negative impacts on soil organisms in some cases. This study aimed to assess the effect of biochar application at rates of 0 (B0), 5 Mg ha−1 (B5), 20 Mg−1 (B20), and 40 Mg ha−1 (B40) on soil nematode community under upland and flooded conditions in a short-term microcosm experiment. After biochar application, soil was incubated for 2 to 8 weeks and nematodes were identified for community composition, trophic structures, functional guilds, maturity index and metabolic footprints. The chemical properties of the soils were also analyzed. General linear model revealed that biochar increased soil pH, EC, NO3−-N, available phosphorus, total C, and C/N ratio, particularly in the highest application rate and shifted the composition of nematodes. The greatest abundances of omnivores (Mesodorylaimus, Thornenema), predator (Nygolaimus) and functional guilds of cp5 were observed in B5, resulting in greatest structure footprint and composite footprint, (omnivorous + predator) footprint and total biomass in B5. While abundances of nematodes tended to decrease with the biochar applicate rates, the abundance of Prismatolaimus was the highest in B40. During the 8-week incubation period, the abundances of Achromadora, Alaimus, Aporcelaimellus, Cryptonchus, Mononchus, and Tobrilus remained stable in upland conditions. Under flooded conditions, the abundances of almost all taxa were markedly lower than those under upland conditions irrespective of biochar application, except for Acrobeloides, Alaimus, Aphelenchoides, and Ditylenchus. We highlighted that 5 Mg ha−1 of rice husk biochar can be the optimum in shaping the nematode community.